2021
DOI: 10.1093/dnares/dsab012
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the speciation history of three sister species of crown-of-thorns starfish (Acanthaster spp.) based on genomic analysis

Abstract: The crown-of-thorns starfish (COTS) is a coral predator that is widely distributed in Indo-Pacific Oceans. A previous phylogenetic study using partial mitochondrial sequences suggested that COTS had diverged into four distinct species, but a nuclear genome-based analysis to confirm this was not conducted. To address this, COTS species nuclear genome sequences were analyzed here, sequencing Indian Ocean (NIO) and Red Sea (RS) species genomes for the first time, followed by a comparative analysis with the Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…3). There is full agreement with initial results that proposed species distinction of the Red Sea clade based on COI data alone (Vogler et al 2008), recently corroborated by nuclear genome analyses (Yuasa et al 2021). The molecular-based species distinction of A. benziei sp.…”
Section: Acanthaster Benziei Sp Nov Wörheide and Kaltenbachersupporting
confidence: 88%
See 3 more Smart Citations
“…3). There is full agreement with initial results that proposed species distinction of the Red Sea clade based on COI data alone (Vogler et al 2008), recently corroborated by nuclear genome analyses (Yuasa et al 2021). The molecular-based species distinction of A. benziei sp.…”
Section: Acanthaster Benziei Sp Nov Wörheide and Kaltenbachersupporting
confidence: 88%
“…These four clades were proposed to represent four species, each with a distinct and largely non-overlapping distribution across the Indo-Pacific region: one from the Red Sea (RS), one from the southern Indian Ocean (SIO), one from the northern Indian Ocean (NIO), and one from the Pacific Ocean (PO) (Vogler et al 2008, see also Vogler et al 2012Vogler et al , 2013. This separation of the RS, NIO and PO species has also been confirmed using a nuclear genome-based analysis, however, the SIO could not be included due to sampling difficulties (Yuasa et al 2021). An in-depth review of the original literature and species descriptions, which aimed to allocate species names to these four genetic clades (Haszprunar & Spies 2014), concluded that A. planci is the valid name for the northern Indian Ocean species, Acanthaster mauritiensis (de Loriol 1885) for the southern Indian Ocean species, and Acanthaster cf.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The Mean Exon Size versus Exon Number and Age of Taxonomic Lineage versus Exon Number were calculated for the following representative animals across metazoan taxa (common name; exon number; mean exon size in base pairs; approximate lineage age in years): phylum Porifera: Amphimedon queenslandica (sponge; 2; 984; 650,000,000 [57]); phylum Brachiopoda: Lingula anatine (lamp shell; 11; 238; 66,000,000 [58]); phylum Hemichordata: Saccoglossus kowalevskii (acorn worm; 9; 234; 373,000,000 [59]); phylum Echinodermata: Acanthaster planci (crown-of-thorns starfish; 11; 404; 4,000,000 [60]), Strongylocentrotus purpuratus (purple sea urchin; 10; 183; 199,000,000 [61]); phylum Cnidaria: Exaiptasia pallida (pale anemone; 4; 544; 500,000,000 [62]), Hydra vulgaris (freshwater polyp; 3; 420; 540,000,000 [63]), Orbicella faveolata (mountainous star coral; 3; 937; 570,000,000 [64]); phylum Mollusca: Octopus bimaculoides (California two-spot octopus; 10; 219; 155,000,000 [65]), Crassostrea gigas (Pacific oyster; 13; 195; 15,000,000 [66]); phylum Arthropoda: Limulus polyphemus (Atlantic horseshoe crab; 6; 206; 250,000,000 [67]), Drosophila melanogaster (fruit fly; 9; 174; 5,400,000 [68]); phylum Chordata: Branchiostoma floridae (Florida lancelet; 7; 154; 100,000,000 [69]), Latimeria chalumnae (West Indian Ocean coelacanth; 10; 181; 70,000,000 [70]), Orcinus orca (killer whale; 10; 182; 11,000,000 [71]), Lipotes vexillifer (Yangtze River dolphin; 10; 170; 11,000,000 [71]), Alligator mississippiensis (American alligator; 10; 210; 53,000,000 [72]), Xenopus laevis (African clawed frog; 11; 173; 18,000,000 [73]), Danio rerio (Zebrafish; 10; 199; 150,000,000 [74]), Monodelphis domestica (gray short-tailed opossum; 10; 196; 3,000,000 [75]), Rattus norvegicus (Norway rat; 10; 178; 2,000,000 [76]), Mus musculus (house mouse; 10; 190; 6,000,000 [77]), Gallus gallus (chicken; 10; 180; 21,000,000 [78]), Pan troglodytes (common chimpanzee; 10; 181; 8,000,000 [79]), Homo sapiens (human; 10; 149; 300,000 [80]). Scatter plots and regression analysis (R 2 : Coefficient of Determination) were generated in Microsoft Excel.…”
Section: Rbm45 Orthologue Gene Architecture Evolutionmentioning
confidence: 99%